Television Mass Media Relations to Culture Shifts in Besilam Malay Community - Marzuki, Datuk Imam; Nasution, Salamudin; Nasution, Salman; Saiful, Muhammad Ikbal; Arroyo-Dean, Estrella T. (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2024)
Media relations with culture can play a role in shifting the views of the Besilam Malay community. This study focuses on the impact of television mass media as a pivotal component of modern society. Technological advancements have placed society at a crossroads, presenting a choice between embracing contemporary progress or adhering to time-honored traditions. The pervasive influence of media serves as a catalyst in shaping awareness and perspectives. The tug-of-war between embracing change and preserving heritage is well exemplified in the traditional berahoi ceremony, which recently has taken up only a small part of the whole tradition. The development of the times that continue to follow renewal can influence people's attitudes and thoughts towards culture supported by technology in the media. This paper used a qualitative research model with a heuristic approach to gather information from cultural and religious community leaders around the Besilam community. This study holds significance in illuminating the ancestral traditions deeply rooted within the Besilam Malay community. It aims to shed light on the evolving nature of these traditions and their transformations over time. Additionally, it serves as a call to action, advocating for the Langkat Regency government to prioritize the preservation of these rich cultural customs. A recommendation is proposed to allocate resources from the APBD Budget Policy through the Tourism Office to sustain and promote these traditions, ensuring their continuity for future generations. Modern Globalization Theory, coined by Wallerstein, asserts that social change occurs as underdeveloped nations emulate the practices and advancements of their more advanced counterparts as a means of progress and growth.